Board gender diversity and firm performance nexus: a literature review of recent research from Nigeria - Ononye, Uzoma Heman; Aloamaka, Judith Ifeanyi (Management and Entrepreneurship: Trends of Development, 2025)
This study aimed to review recent empirical research on the relationship between board gender diversity (BGD) and firm performance, with a specific focus on the Nigerian context. The study employed a literature review based on 24 empirical studies. The peer-reviewed articles were searched and extracted from the Google Scholar and African Journals Online databases. The study meticulously analysed the 24 articles to provide an overview of the current relationship between BGD and firm performance. The articles included in this review were peer-reviewed empirical papers with a focus on Nigeria, published not earlier than 2020. The review indicated that a majority of the articles supported the significant and positive effect of BGD on firm financial performance. Our results demonstrate the considerable attention paid to financial performance compared to other performance aspects. However, literature emphasized the importance of BGD for furthering social and environmental performance. Therefore, BGD contributes to different firm performance parameters. The review also highlighted that the empirical evidence of the relationship is fragmented, yet studies have not fully articulated the contextual influences by identifying mediators and moderators. In this regard, research has not evolved substantially beyond the simple linear relationship, which limits the ability to develop and internalize best practices with wide acceptance and application. A linear research focus contributes to the uncertainty about the performance benefits of BGD, providing limited insights for the Nigerian firms. To make progress in research, future studies should be informed by the need to enhance our understanding of how BGD affects firm performance and whether it plays other contextual roles that impact firm performance. This is the first study to review recent empirical research on BGD and firm performance in Nigeria, thereby enhancing our current understanding by integrating the findings of various studies. JEL Classification: M10, M140, L250